Upaya Peningkatan Kreativitas dan Karakter Anak Islami melalui Lomba Kreasi Santri di TPQ Al Muttaqin Desa Kayen - Yessita Puspaningrum; Siti Aminatuz Zuhria; Muhammad Sulton; Mohammad Baharudin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this community service activity is to foster the spirit of students in studying religion and increase the self-confidence of the students. This community service activity was located at the TPQ Al Muttaqin Foundation in Kayen Village, Bandarkbuildingmulyo District, Jombang Regency. This activity was carried out in October 2020 with a total of approximately 35 students. The approach method for the implementation of community service activities was in the form of socialization, training and holding student creation competition activities in the context of the 2020 Santri Day commemoration with the TPQ Al Muttaqin children to foster the enthusiasm and motivation of the students in Islamic activities. The competitions that were held included: coloring competition, memorizing competition of short letters, and adzan competition. The evaluation of the results of the activities showed that the students admitted that they were happy with this competition because they were given a forum for self-development in acclimating Islamic character. The students also claimed to be more motivated in carrying out religious activities such as praying 5 times in congregation.